1993
DOI: 10.4049/jimmunol.150.10.4659
|View full text |Cite
|
Sign up to set email alerts
|

HLA A2 restricted cytotoxic T lymphocyte responses to multiple hepatitis B surface antigen epitopes during hepatitis B virus infection.

Abstract: Inasmuch as the hepatitis B virus (HBV) is not directly cytopathic for the infected hepatocyte, it is generally presumed that viral clearance and liver cell injury during viral hepatitis are due to a CTL response to HBV encoded Ag presented by HLA class I molecules. We have previously examined the peripheral blood CTL response to two HBV nucleocapsid epitopes in patients with acute and chronic viral hepatitis, one of which is restricted by HLA-A2, whereas the other is dually restricted by HLA-A31 and Aw68. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1994
1994
2009
2009

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 308 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The second is HBsAg-reactive cytotoxic T cells. In most patients with acute hepatitis, CTL responds to epitopes of HBsAg, while there are no such responses in patients with chronic hepatitis .Thus, Th1 might be insufficient for complete removal of HBV in chronic hepatitis but positively correlated with hepatic inflammatory activity 13 . In contrast to our study, Castillo et al, 14 found that the normal levels of IFN-g in the patient's sera with acute HBV infection was explained by that, the DNA viruses are poor inducer of IFN-g. On the other hand Priimangi et al 15 reported that IFN-g increased during chronic viral infection, he suggested that such cytokine involved in the pathogenesis of chronic HBV liver disease.…”
Section: Ifnmentioning
confidence: 99%
“…The second is HBsAg-reactive cytotoxic T cells. In most patients with acute hepatitis, CTL responds to epitopes of HBsAg, while there are no such responses in patients with chronic hepatitis .Thus, Th1 might be insufficient for complete removal of HBV in chronic hepatitis but positively correlated with hepatic inflammatory activity 13 . In contrast to our study, Castillo et al, 14 found that the normal levels of IFN-g in the patient's sera with acute HBV infection was explained by that, the DNA viruses are poor inducer of IFN-g. On the other hand Priimangi et al 15 reported that IFN-g increased during chronic viral infection, he suggested that such cytokine involved in the pathogenesis of chronic HBV liver disease.…”
Section: Ifnmentioning
confidence: 99%